PENERAPAN SISTEM SINGLE IDENTITY NUMBER SETELAH PEMBERLAKUAN PERATURAN NIK MENJADI NPWP - Citra Alfa Esi Pabeta; Omega Avriella; Cindi Septiani; Sherlina Mike; Carolus Askikarno Palalangan (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
The implementation of the Single Identity Number System after the implementation of the new regulation on changing NIK to NPWP in Indonesia will enter a period of a new administrative system which is made easier through a system of using only one identity card that can be used for administrative needs. The Single Identity Number is a system for identifying a person using a NPWP from those who originally used a NIK. The advantage of implementing a Single Identity Number is that it can simplify the administration system in the field of taxation and strengthen it. Source database for government. The purpose of this research is to analyze the estimation of the fulfillment of the Simplified Single Identity Number concept. This is in accordance with the applicable law, namely Law no. 7 of 2021 article 2 paragraph 10 which states the Harmony of the Tax System in Indonesia. A qualitative approach is used as a research method with interview techniques to collect data. The research subjects were people who were randomly selected. The conclusion of this study is a Single Identity Number can meet customer needs and simplify the tax administration system in Indonesia.